Forest Fragments Surrounded by Sugar Cane Are More Inhospitable to Terrestrial Amphibian Abundance Than Fragments Surrounded by Pasture. (14th December 2013) - D'Anunciação, Paula Eveline Ribeiro; Silva, Marcela Fernandes Vilela; Ferrante, Lucas; Assis, Diego Santana; Casagrande, Thamires; Coelho, Andréa Zalmora Garcia; Amâncio, Bárbara Christina Silva; Pereira, Túlio Ribeiral; da Silva, Vinícius Xavier
Abstract : In recent years, there has been increasing interest in matrix-type influence on forest fragments. Terrestrial amphibians are good bioindicators for this kind of research because of low vagility and high philopatry. This study compared richness, abundance, and species composition of terrestrial amphibians through pitfall traps in two sets of semideciduous seasonal forest fragments in southeastern Brazil, according to the predominant surrounding matrix (sugar cane and pasture). There were no differences in richness, but fragments surrounded by sugar cane had the lowest abundance of amphibians, whereas fragments surrounded by pastures had greater abundance. The most abundant species, Rhinella ornata, showed no biometric differences between fragment groups but like many other amphibians sampled showed very low numbers of individuals in fragments dominated by sugar cane fields. Our data indicate that the sugar cane matrix negatively influences the community of amphibians present in fragments surrounded by this type of land use.